The Nexus Between Rural Bank Performance and Growth of Regional Gross Domestic Product in Depok, West Java - Nisa, Chaerani; Muhammad Nuruddin Subhan; Tyahya Whisnu Hendratni; Yohana Oentarjo (Dinasti Publisher, 2024)
This research examines the relationship between rural bank performance and regional GDP growth in Depok, West Java. Research data was collected from the Financial Service Authority website and the Central Bureau of Statistics Depok. The collected data covers 25 rural banks in Depok with a time span between the first quarter of 2017 to the first quarter of 2022. The research uses panel data, which is then regressed using a random effect model. The research results show that the Capital Adequacy Ratio and Loan Deposit Ratio have a positive impact on regional GDP growth. These findings show that healthy rural bank conditions will encourage economic growth. Therefore, a good policy atmosphere and supervision are needed to create healthy rural banks.